Pengaruh Orientasi dengan Metode Perceptorship dan Mix Staffing terhadap Mutu Layanan Keperawatan - Yuli Yanti; Muhammad Hadi; Rohadi Haryanto (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to obtain a description of the quality of nursing services before and after orientation with the preceptorship and mix staffing methods at Pasar Minggu South Jakarta Hospital 2018. This research method is a quantitative study with a quasi-experimental research type with pre and post with control group design. The results showed that statistically there were differences between the quality of nursing services before and after the intervention intervention of the preceptorship and mix staffing methods (p <0.05). The analysis also showed that there were differences in the quality of nursing services in the control group from the 1st, 2nd, 3rd and 4th observations (p <0.05). The conclusion of this research is the orientation of the preceptorship and mix staffing methods is very potential in improving the quality of nursing services in hospitals. Keywords: Mix Staffing, Quality of Nursing Services, Preceptorship